“Ejercicios fisioterapéuticos y su influencia en la recuperación de la bursitis de hombro en adultos entre 30 y 40 años del cantón Baba Los Ríos. Septiembre 2017 a febrero 2018”. - Montece Ortega, Darwin Leonardo (2018)
The present study is aimed at 310 Baba Canton patients suffering from shoulder bursitis injury in adults between the ages of 30 and 40 years and the effects on the application of physiotherapy exercises as rehabilitation treatment. The objective is to determine the influence of physiotherapy exercises in the recovery of shoulder bursitis in adults between 30 and 40 years of the Baba county, province of Los Ríos. September 2017 to February 2018 in order to design a tool to identify and replace activities that may generate shoulder bursitis, which will benefit the inhabitants of the Baba canton so they can have a better quality of life by reducing chronic cases. The application of the research methods allowed to classify and statistically organize the data obtained and it will facilitate us to obtain the interpretation as an index of the physiotherapy exercises that lead to the recovery of bursitis in adults between 30-40 years. The highest level was obtained as a result of the criteria of the health professionals, with 80% always showing total recovery of the affected shoulder with bursitis. It was observed that performing the three weekly sessions of the physiotherapy exercises increased the degree of mobility and decreased the pain of the affected shoulder, the improvement was notably in the subjects investigated